Solvent-dependent aggregation behavior of a new Ru(ii)-polypyridyl based metallosurfactant - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chemical Communications, 2011)
Variation of the solvent polarity leads to the formation of vesicles and reverse vesicles of a newly synthesized amphiphilic Ru(II)-polypyridyl complex.

Studies on [3]pseudorotaxane formation from a bis-azacrown derivative as host and imidazolium ion-derivatives as guest - Mandal, Amal Kumar; Suresh, Moorthy; Das, Amitava (Organic & Biomolecular Chemistry, 2011)
A new host molecule, having two azacrown derivatives bridged by luminescent naphthalene diimide functionality, is found to form a [3]pseudorotaxane derivative with imidazolim ion-based guest molecules in non-polar solvents through hydrogen-bonded adduct formation. Depending upon the length of the covalent linker that links the imidazolium ion and the luminescent naphthalene fragment in the guests, the [3]pseudorotaxane adducts adopt different conformation or orientation with varying π–π/donor–acceptor interaction. The mechanism for the naphthalene-based luminescence quenching by NDI fragment on adduct formation was found to be a combination of static, as well as dynamic with static quenching as the dominant one.

Sequential energy and electron transfer in polynuclear complex sensitized TiO2 nanoparticles - Verma, Sandeep; Kar, Prasenjit; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry Letters, 2012)
Polynuclear–polypyridyl complexes exhibit a directional energy-transfer property that can improve their photosensitization activity. In the present work, the energy-transfer process is explored in a trinuclear Ru2∧Os1 complex using transient absorption spectroscopy. This study reveals an efficient excitation energy transfer from the terminal (RuII complex) to the core (OsII complex) region in the ultrafast time domain (400 fs–40 ps). The excitation energy funnel is useful in improving the functionalized core activity. This is evidenced in an interfacial electron-transfer study of Ru2∧Os1, Ru2∧Ru1, and Os1 complex sensitized TiO2 nanoparticle (TiO2 NP) systems. The intramolecular energy transfer causes sequential excitation of the core part of the Ru2∧Os1 complex, which leads to multiexponential electron injection into TiO2 NP. Besides this, the electronic coupling between the metal ion centers stabilizes the positive charge within the trinuclear complex, which results in a slow charge recombination reaction. This study shows that polynuclear complexes can be very useful for their panchromatic effects, unidirectional energy- and electron-transfer properties.

Self-assembly of modified rhodamine-6G with tri-block copolymer: unusual vesicles formation, pH sensing and dye release properties - Praveen, L.; Saha, Sukdeb; Jewrajka, Suresh K.; Das, Amitava (Journal of Materials Chemistry B, 2013)
A new rhodamine-6G derivative having a C18-alkyl chain self-assembles with an amphiphilic tri-block copolymer and forms stable vesicles in water or in water–ethanol (4 : 1, v/v) medium. The stability of the spirolactam form of the rhodamine-6G derivative in these vesicular structures, along with studies of controlled dye release and pH sensing are discussed. Transmission electron micrographs and DLS analyses confirm the formation of vesicular structures. Atomic force microscopy (AFM) images show that the self assembled tri-block copolymer-octadecyl rhodamine vesicles form near spherical nanostructures with a size ranging from 80 to 110 nm. Furthermore, the vesicular system is disassembled under acidic conditions, releasing the cargo which are an integral part of the vesicle. Dye-release studies showed that the release rates of the loaded dye in the vesicles could be well-controlled as a function of the media pH. These results offer an opportunity to use these nanovesicles as imaging reagents for probing media pH with their simultaneous use as nanocarriers for intracellular drug delivery.

Synthesis, steady-state, and femtosecond transient absorption studies of resorcinol bound ruthenium(ii)- and osmium(ii)-polypyridyl complexes on nano-TiO2 surface in water - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Inorganic Chemistry, 2013)
The synthesis of two new ruthenium(II)- and osmium(II)-polypyridyl complexes 3 and 4, respectively, with resorcinol as the enediol anchoring moiety, is described. Steady-state photochemical and electrochemical studies of the two sensitizer dyes confirm strong binding of the dyes to TiO2 in water. Femtosecond transient absorption studies have been carried out on the dye–TiO2 systems in water to reveal <120 fs and 1.5 ps electron injection times along with 30% slower back electron transfer time for the ruthenium complex 3. However, the corresponding osmium complex 4 shows strikingly different behavior for which only a <120 fs ultrafast injection is observed. Most remarkably, the back electron transfer is faster as compared to the corresponding catechol analogue of the dye. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This Article on the electron transfer dynamics of the aforesaid systems reinforces the possibility of resorcinol being explored and developed as an extremely efficient binding moiety for use in dye-sensitized solar cells.

Size quantization effects on interfacial electron transfer dynamics in Ru(II)-polypyridyl complex sensitized ZnO QDs - Verma, Sandeep; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2014)
Quantum-size confinement in semiconductor material offers size based tunability of interband gap energy as well as intraband sublevels. In this work, size quantization of wide bandgap ZnO quantum dots has been explored in the study of interfacial charge separation reaction using a catechol functionalized Ru(II)polypyridyl complex as a photosensitizer molecule. Femtosecond time-resolved transient absorption studies have revealed multiple electron injection events based on discrete conduction band states of ZnO QDs. The electron injection rates have been rationalized for quantum confinement effects owing to different sizes of ZnO QDs. Furthermore, the size dependency of the intrinsic lifetime of electrons injected into discrete energy levels of ZnO QDs has been revealed in charge recombination reaction with the Ru(III)polypyridyl complex cation. The charge recombination dynamics reveals a competing trend of carrier confinement and carrier leak upon reducing particle size. This study shows the optimization of finite size effects in achieving better interfacial charge separation at the dye/semiconductor interface.

Specific probe for Hg2+ to delineate even H+ in pure aqueous buffer/Hct116 colon cancer cells: Hg(II)-eta(2)-arene pi-interaction and a TBET-based fluorescence response - Reddy, Upendar G.; Ramu, Vadde; Roy, Sovan; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2014)
A new molecular probe that demonstrates a distinct TBET process, induced by the Hg(II)-eta(2)-arene pi-interaction, in pure aqueous medium with a large pseudo-Stokes shift of 200 nm.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).

Specific receptor for hydrazine: mapping the in situ release of hydrazine in live cells and in an in vitro enzymatic assay - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Mogare, Devraj G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2016)
We report a new chemodosimetric reagent capable of detecting hydrazine in the presence of several other competing amine derivatives and ionic analytes of biological relevance. This reagent has been utilized for real time monitoring of in situ N2H4 release during the metabolism of a crucial tuberculosis drug, isoniazid, in live HepG2 cells. The fluorescence response of the reagent based on its specific reaction with N2H4 is used for developing an in vitro assay for aminoacylase-1.

Switch-on NIR probe for specific detection of Hg2+ ion in aqueous medium and in mitochondria - Agarwalla, Hrideshg; Mahajan, Pankaj S.; Sahu, Debashis; Taye, Nandaraj; Ganguly, Bishwajit; Mhaske, Santosh B.; Chattopadhyay, Samit; Das, Amitava (Inorganic Chemistry, 2016)
A new 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY)-based probe molecule (L) is synthesized for specific binding to Hg2+ ion in physiological condition with an associated luminescence ON response in the near-IR region of the spectrum. Appropriate functionalization in the 5-position of each of two pyrrole moieties with styryl functionality in a BODIPY core helped us in achieving the extended conjugation and a facile intramolecular charge transfer transition with a narrow energy gap for frontier orbitals. This accounted for a poor emission quantum yield for the probe molecule L. Binding to. Hg2+ helped in interrupting the facile intramolecular charge transfer (ICT) process that was initially operational for L. This resulted in a hypsochromic shift of absorption band and a turn-on luminescence response with lambda(Em)(max) of 650 nm on specific binding to Hg2+. Observed spectral changes are rationalized based on quantum chemical calculations. Interestingly, this reagent is found to be localized preferentially in the mitochondria of the live human colon cancer (Hct116) cells. Mitochondria is one of the major targets for localization of He2+, which actually decreases the mitochondrial membrane potential and modifies various proteins having sulfudryl functionality(ies) to cause cell apoptosis. Considering these, ability of the present reagent to specifically recognize Hg2+] in the mitochondrial region of the live Hct116 cells has significance.

Super-resolution probe to monitor HNO levels in the endoplasmic reticulum of cells - Ali, Firoj; Sreedharan, Sreejesh; Ashoka, Anila Hoskere; Saeed, Hiwa K.; Smythe, Carl G. W.; Thomas, Jim A.; Das, Amitava (Analytical Chemistry, 2017)
Selective detection of nitroxyl (HNO), which has recently been identified as a reactive nitrogen species, is a challenging task. We report a BODIPY-based luminescence ON reagent for detection of HNO in aqueous solution and in live RAW 264.7 cells, based on the soft nucleophilicity of the phosphine oxide functionality toward HNO. The probe shows high selectivity to HNO over other reactive oxygen/nitrogen and sulfur species. Luminescence properties of the BODIPY-based chemodosimetric reagent make it an ideal candidate for use as a reagent for super-resolution structured illumination microscopy. The viability of the reagent for biological in vivo imaging application was also confirmed using Artemia as a model.